Ultrasound guidance versus classical method for intrauterine insemination - Abdulwahab, Aliaa Saleh; Sharief, Maysoon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: There are a wide range of treatment options available for unexplained infertility, such as expectant management, superovulation, intrauterine insemination (IUI) and In vitro fertilization (IVF). So, the objective was to compare clinical pregnancy rates in IUI with transabdominal ultrasound guidance (US-IUI) versus the “blind method” IUI. Methods: This was a randomized controlled trial done at Basrah Maternity and Child Hospital/IVF Center during the period between 01 January 2020 till 01 March 2023. 130 couples with unexplained infertility were included. All couples underwent infertility assessment in day 2 or day 3 basal serum follicle-stimulating hormone (FSH) levels and serum luteinizing hormone (LH) levels. Patients were divided randomly into 2 groups; 1ST group (70 women) underwent IUI with transabdominal ultrasound guidance while the 2nd group (60 women) undergoing IUI without ultrasound guidance. Results: The mean age of the patients was 30.6 ± 4.0 years (range 25-40). Of the 267 cycles, 145 were carried out as US-guided and 122 were performed using the blind procedure. The overall pregnancy rate was 17%; one pregnancy were multiple pregnancies and 1 ended in abortion. There was no significant difference between the US-guided and blinded IUI groups regarding the multiple-pregnancy rate, abortion rate. The pregnancy rates were 23.4% and 13.9% respectively and the difference was statistically significant (p=0.049). In the US-guided group, 9.7% of the cases were difficult. In the blinded group, 26.2% were difficult. Conclusions: The conventional blind method for intrauterine catheter insemination is recommended for patients undergoing IUI treatment.